Ethical principles for the introduction and use of modern technologies in academic work - Chen, Lin; Saharuddin, Norzihani; Abdullah, Nur Surayyah Madhubala (Routledge, 2025)
This study aimed to reflect on and develop ethical principles and practices for the responsible introduction and use of modern technologies in the academic environment. The study uncovered ethical principles and practices for the use of modern technology in the academic environment. The following key aspects of ethics in the context of technology use were identified: transparency, accountability, credibility, fairness, and equity. The effectiveness of using learning management systems (LMS), virtual laboratories, and artificial intelligence (AI) to improve the quality of education and research was demonstrated through examples of successful technology implementation in universities, highlighting the necessity of these principles to maintain trust and cooperation in educational institutions and ensure access to educational resources for all participants. The study identified a number of challenges including data privacy, academic integrity, uneven access to technology, and the need for continuous learning.